Growth performance, amino acid retention and mRNA levels of mTORC1 signaling pathway genes in Nile tilapia fingerlings fed protein-bound and crystalline amino acids - da Cruz, Thaís Pereira; Michelato, Mariana; Dal-Pai-Silva, Maeli [UNESP]; de Paula, Tassiana Gutierrez [UNESP]; Macedo, Edson Assunção; Peres, Helena; Oliva-Teles, Aires; Urbich, Allan Vinnicius; Furuya, Valéria Rossetto Barriviera; Furuya, Wilson Massamitu (Elsevier, 2021)
Recent research has provided new mechanistic insights that amino acids (AA) coordinate protein synthesis by expressing the evolutionarily conserved target of rapamycin complex 1 (mTORC1) signaling pathway genes. An 8-week feeding trial was conducted to evaluate the impacts of experimental diets (420 g kg−1 crude protein; 15 MJ g kg−1) with protein-bound AA (Control), crystalline amino acids (CAA) supplemented at 60 g kg−1 and CAA at 120 g kg−1 on growth performance, AA retention, and mTORC1 signaling pathway (mTOR, mLST8, and Raptor) genes in Nile tilapia, Oreochromis niloticus fingerling (n = 360; 4.3 ± 0.1). At the end of feeding trial, the time-course postprandial plasmatic lysine and methionine were determined by collecting blood samples of fish immediately after feeding and at 60, 120, 240, 480 and 960 min. Each diet was randomly distributed into eight replicates groups of 12 fish and hand-fed, six times a day until apparent satiety for eight weeks. Compared with fish fed CA120 diet, body weight gain (BWG), feed intake (FI), feed efficiency (FE), protein retention efficiency (PRE) and retention of six essential and five non-essential AA parameters were improved in fish fed Control and CA60 diets. Furthermore, fish fed CA60 diet showed significantly lower whole-body lipids and higher crude protein than those fed other diets, whereas humidity and ash were not affected by dietary treatments. Plasmatic lysine and methionine linearly increased in fish fed Control diet. However, time-course plasmatic lysine and methionine were affected along with quadratic effect, and plasmatic lysine and methionine peaked at 461 and 496 min in fish fed CA60 diet, being reduced at 364 and 405 min in fish fed CA120 diet, respectively. The mechanistic insights of well-balanced AA coordinating protein synthesis in fish fed Control and CA60 diets was identified through a similar response on relative gene expression of mLST8 and mTOR genes, but higher than that in fish fed CA120 diet. Overall, this study validated CAA up to 60 g kg−1 without adverse effects on fish growth performance. However, a high CAA level at 120 g kg−1 depressed growth performance and may be considered to produce industrial-scale feeds for precision tilapia feeding. Statement of relevance: This study revealed new mechanistic insights that amino acids regulate protein synthesis through genomic approaches by regulating relative gene expression of mTORC1 signaling pathway. The data is relevant to the formulation of well-balanced amino acids precision tilapia feeding.
Keywords: crystalline amino acids; mTORC1 pathway; nitrogen excretion; Oreochromis niloticus; protein synthesis